1982
DOI: 10.1111/j.1476-5381.1982.tb09278.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacological Analysis of the Hyperactivity Syndrome Induced by Β‐phenylethylamine in the Mouse

Abstract: 1 The effects of the putative 5-hydroxytryptamine (5-HT) receptor antagonists, methysergide, mianserin and methergoline, the dopamine receptor antagonists, haloperidol, thioridazine and clozapine, and the noradrenaline (NA) receptor antagonists, phentolamine, phenoxybenzamine and propranolol on the behavioural responses of mice to 3-phenylethylamine (PEA, 75 mg/kg) have been examined. 2 PEA produced a syndrome consisting of three distinct phases. The brief initial phase (0-5 min after injection) which consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…Our results have shown that PEA produced a monophasic stimulant effect per se and this response in rats differs from that seen in mice where an initial hypermotility, followed by depression then a secondary hypermotility, has been observed (Jackson 1972;Dourish 1982). The early stimulant phase in mice at least is thought to be dependent on intact pathways and receptors for DA and NA, while the late stimulation is due to a direct agonist action on post-synaptic dopamine receptors (Jackson 1975(Jackson , 1978.…”
Section: Discussioncontrasting
confidence: 50%
“…Our results have shown that PEA produced a monophasic stimulant effect per se and this response in rats differs from that seen in mice where an initial hypermotility, followed by depression then a secondary hypermotility, has been observed (Jackson 1972;Dourish 1982). The early stimulant phase in mice at least is thought to be dependent on intact pathways and receptors for DA and NA, while the late stimulation is due to a direct agonist action on post-synaptic dopamine receptors (Jackson 1975(Jackson , 1978.…”
Section: Discussioncontrasting
confidence: 50%
“…In rodents PEA elicits AMPH-like behavior (Hirano et al, 1989;Janssen et al, 1999) at doses of ∼50 mg/kg (intraperitoneal) characterized by hyperactivity, occasional walking backward, rearing, sniffing, gnawing, and licking (Dourish, 1982;Boulton, 1982;Lapin, 1996). At higher doses (75-100 mg/kg) repetitive, stereotypical behaviors, predominate including 'wet dog' shaking, excessive grooming and head movement, seizures, labored breathing, salivation, and straub tail.…”
Section: 43mentioning
confidence: 99%
“…Furthermore, pharmacologic manipulations (Borison et al, 1974;Borison et al, 1975;Boulton, 1976a;Philips & Boulton, 1979;Stoff et al, 1984;Boulton et al, 1990;Juorio et al 1991a;Juorio et al 1991b) and lesioning studies Juorio & Jones, 1981;Greenshaw et al, 1985;Greenshaw et al, 1986;Greenshaw et al, 1986;Juorio et al, 1987; can significantly influence TA turnover and levels with physiological (Becu-Villalobos, 1987;Cheng, 1990;Hirashima, 1999;Lee et al, 2003) and behavioral (Dourish, 1982;Lapin, 1996;Rex et al, 2004;Suo et al, 2006) consequences.…”
Section: Historic Contextmentioning
confidence: 99%
“…In rodents, β‐PEA produces a robust behavioral phenotype consisting of short‐term stimulation of locomotor activity and stereotypy as well as a plethora of peripherally mediated effects (Dourish 1982; Boulton 1982; Saavedra 1989; Lapin 1996). Neurochemical characterization of this psychostimulant action leads to two major hypotheses.…”
mentioning
confidence: 99%